QUALITATIVE AND QUANTITATIVE ANALYSIS OF SILDENAFIL IN TRADITIONAL MEDICINES AND DIETARY SUPPLEMENTS - Podder, Ashis Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Use of traditional medicines as aphrodisiac and sex stimulant products is a common phenomenon worldwide as well as in our country. In addition to that, in the name of dietary supplements, a number of urban people are using these items as the source of their sex potential. These products ought to be responsible for raising several sexual violence and perversion in the society. A simple, precise, specific, accurate, robust, cost-effective and validated reversed phase high performance liquid chromatography (RP-HPLC) method was developed according to USP and ICH (Q2 R1) guidelines to determine sildenafil in the collected samples. Chromatography was carried out using a C18 column with a mobile phase composed of (diluted sulfuric acid : acetonitrile = 60:40) and detected at the wavelength of 290nm. Presence of sildenafil in the identified products was further confirmed by infrared (IR) spectroscopy. In the study, found that 5 out of 25 traditional medicines and 7 out of 10 dietary supplements contain sildenafil. In addition to that 4 out of total 35 samples were found to contain sildenafil that was exceeding the highest dose (100mg per dosage unit) recommended by the manufacturer (Pfizer,UK) of the brand product ViagraTM. Notably all the samples were labelled to contain only natural ingredients rather than sildenafil.